Terrengordet avløype - Bratt, Jesse (NAMN OG NEMNE, 2022)
This article tries to find the meaning of the word avløype. The word is undocumented in dictionaries, but is used in 157 places names in Western Norway. It may once have used to describe shore areas between the high-water mark and low-water mark. But many places the names denote do not match this description today. The article’s analysis is based on a review of the literature, metadata from name archives, maps of the places the names denote, and letters from local historical societies.